Mulheres bolivianas na política: limites e possibilidades da constituição plurinacional - Lira, Thariny Teixeira (Universidade Federal Rural do Semi-Árido, 2021)
This research aims to analyze, from a Marxist feminist perspective, the limits and possibilities of the Bolivian constitutional transformations in the theme of women's participation in institutional politics. Therefore, we discuss the multiple feminist strands and what will be our theoretical emphasis to carry out the intended analysis. We focused on the processes of struggles that led to the achievement of parity between men and women in Bolivian state spaces, especially in parliament. We present an overview of the plurality of women's organizations in Bolivia, highlighting the work of Bartolinas Sisa indigenous peasants, a determinant organization for the elevation of gender equality as one of the founding values of the Plurinational State. We present the constitutional innovations of the Plurinational State of Bolivia on the theme of gender equity, women's rights and equality between men and women in institutionality, analyzing and interpreting these provisions hermeneutically and historically. From a theoretical point of view, we understand that the legal and political phenomenon that involves the issue of Bolivian women in institutionality requires a totalizing reading. Thus, the Marxist approach imposes itself as the most adequate analytical tool. The study is qualitative and theoretical, using as methodological procedures the bibliographical review on the subject, in addition to the documental analysis of the Constitution of the Plurinational State of Bolivia, as well as the mobilization of other data that support the intended argumentation. Finally, we conclude that the constitutional changes, despite being important, do not have the power to guarantee the human emancipation of Bolivian women, due to the very nature of the legal form
Keywords: Feminismo Marxista; Participação das Mulheres na Política; Estado Plurinacional da Bolívia; Marxist Feminism; Women's Participation in Politics; Plurinational State of Bolivia; CIENCIAS SOCIAIS APLICADAS::DIREITO